Plasma Membrane Calcium ATPases as Novel Candidates for Therapeutic Agent Development - Emanuel E Strehler (Frontiers Media S.A., 2013)
Plasma membrane Ca2+ ATPases (PMCAs) are highly regulated transporters responsible for Ca2+ extrusion from all eukaryotic cells. Different PMCA isoforms are implicated in various tasks of Ca2+ regulation including bulk Ca2+ transport and localized Ca2+ signaling in specific membrane microdomains. Accumulating evidence shows that loss, mutation or inappropriate expression of different PMCAs is associated with pathologies ranging from hypertension, low bone density and male infertility to hearing loss and cerebellar ataxia. Compared to Ca2+ influx channels, PMCAs have lagged far behind as targets for drug development, mainly due to the lack of detailed understanding of their structure and specific function. This is rapidly changing thanks to integrated efforts combining biochemical, structural, cellular and physiological studies suggesting that selective modulation of PMCA isoforms may be of therapeutic value in the management of different and complex diseases. Both structurally informed rational design and high-throughput small molecule library screenings are promising strategies that are expected to lead to specific and isoform-selective modulators of PMCA function. This short review will provide an overview of the diverse roles played by PMCA isoforms in different cells and tissues and their emerging involvement in pathophysiological processes, summarize recent progress in obtaining structural information on the PMCAs, and discuss current and future strategies to develop specific PMCA inhibitors and activators for potential therapeutic applications. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.